Hei Tech Excellence Award belongs to Nur Sofhia Izzaty - Siti Nurfarmy, Ibrahim (UMPSA, 2024)
GAMBANG, 27 October 2024 – “Hold your vision, trust the process,” and believing in the prayers of her parents are the principles and guiding words always upheld by Nur Sofhia Izzaty Mohamad Azizi, 23, a graduate of the Bachelor of Computer Science (Software Engineering) with Honours, Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA).